Impact of continuous glucose monitoring on glycemic control and its derived metrics in type 1 diabetes: a longitudinal study - Cho, So Hyun; Kim, Seohyun; Lee, You-Bin; Jin, Sang-Man; Hur, Kyu Yeon; Kim, Gyuri; Kim, Jae Hyeon (Frontiers in Endocrinology, 2023)
Aim We explored the effectiveness of continuous glucose monitoring for 1 year on glycated A1c reduction in adults with type 1 diabetes mellitus. Methods We included type 1 diabetes mellitus adults who were either new continuous glucose monitoring users (N = 155) or non-users who were under standard care (N = 384). Glycated A1c was measured at baseline and 3, 6, 9, and 12 months. Individuals with (N = 155) or without continuous glucose monitoring use (N = 310) were matched 1:2 by propensity score. We used the linear mixed models to identify the quantitative reduction in repeated measures of glycated A1c. Results The change in glycated A1c from baseline to 12 months was −0.5% ± 1.0% for the continuous glucose monitoring user group (N = 155, P < 0.001) and −0.01% ± 1.0% for the non-user group (N = 310, P = 0.816), with a significant difference between the two groups (P = 0.003). Changes in glycated A1c were significant at 3, 6, 9, and 12 months compared with those at baseline in patients using continuous glucose monitoring (P < 0.001), and the changes differed significantly between the groups (P < 0.001). A linear mixed model showed an adjusted treatment group difference in mean reduction in glycated A1c of −0.11% (95% confidence interval, −0.16 to −0.06) each three months. In the continuous glucose monitoring user group, those who achieved more than 70% of time in range significantly increased from 3 months (37.4%) to 12 months (48.2%) (P < 0.001). Conclusion In this longitudinal study of type 1 diabetes mellitus adults, the use of continuous glucose monitoring for 1 year showed a significant reduction in glycated A1c in real-world practice.